Similarity of nucleotide interactions of BiP and GTP-binding proteins. - Brot, N (1994)
BiP is a member of the Hsp70 heat shock protein family found in the lumen of the endoplasmic reticulum, that binds to a variety of proteins destined to be secreted. Substance P (SP) has been used as a model peptide to study the interaction of BiP with protein substrates. SP stimulates BiP ATPase activity and forms a stable complex with BiP that is dissociated in the presence of levels of ATP > 50 microM. At lower concentrations of ATP, the SP remains bound to BiP, and the results are consistent with the view that a BiP-ATP complex is initially formed that reacts with SP to form a ternary complex, SP-BiP-ATP. Hydrolysis of ATP in this complex yields a SP-BiP-ADP complex. An exchange of ATP with ADP bound to BiP has also been demonstrated, and the results suggest that the interactions of BiP with ATP resemble those seen with GTP-binding proteins and GTP.